Enhancing finger sensitivity: Sensory-based Activity Module (Sensory-BAM) - Khairil Anuar, Khairina Iqlima Batrisyia; Izharruzzahir, Nurinsyirah Najihah; Sajab, Mohd Shaiful; Kaco, Hatika (Academica Press Solutions, 2023)
Visual impairment and blindness constitute a prevalent global health concern, significantly impacting individuals with visual impairments and those in their immediate vicinity, thereby exerting a substantial societal disability. Sighted individuals do not encounter the same range of difficulties in their daily routines and learning as those faced by individuals with visual impairments. Nevertheless, despite the obstacles they encounter, individuals with visual impairments heavily rely on their tactile and auditory senses to gather information from the environment. As a result, they may necessitate assistance or utilize tools that can enhance their sensory acuity. Consequently, engaging in sensory activities enables individuals with visual impairments to enhance their finger sensitivity, thus facilitating sensory exploration. Consequently, the objective of this study was to investigate the potential of integrating sensory activity in the form of a module with game-based activities as a means of enhancing finger sensitivity. This was achieved by creating a sensory based activity module (sensory-BAM) that could be used to instruct individuals on how to improve their finger sensitivity. Sensory-BAM utilizes tactile activities and integrates various skills, including communication, leadership, teamwork, and creativity to achieve the learning outcomes a) increase finger sensitivity, b) recognize the texture of the materials used and c) increase hand’s strength. Therefore, a series of activities were organized, with each activity station offering a unique game that utilized different materials, such as sand, rice, fingerpaint, and playdough with different missions. Every prepared activity was centered around a tactile experience that is appropriate for enhancing finger sensitivity. Sensory-BAM consists of four game stations prepared for all participants including sand, paint, playdough and rice as the main item for improving finger sensory. Ergo, this engaging activity-game learning approach provides visually impaired individuals with a practical way to improve their tactile sensitivity and specially for visually impaired in learning Braille.